Cross-Cultural Communication on Social Media: Review From the Perspective of Cultural Psychology and Neuroscience - Yuna, Di; Xiaokun, Liu; Jianing, Li; Lu, Han (Frontiers in Psychology, 2022)
Introduction: In recent years, with the popularity of many social media platforms worldwide, the role of "virtual social network platforms " in the field of cross-cultural communication has become increasingly important. Scholars in psychology and neuroscience, and cross-disciplines, are attracted to research on the motivation, mechanisms, and effects of communication on social media across cultures. Methods and Analysis: This paper collect the co-citation of keywords in "cultural psychology", "cross-culture communication", "neuroscience" and "social media" from the database of web of science and analyzes the hotspots of the literatures in word cloud. Results: Based on our inclusion criteria, 85 relevant studies were extracted from a database of 842 papers. There were 44 articles on cultural communication on social media, of which 26 were from the perspective of psychology and five from the perspective of neuroscience. There are 27 articles that focus on the integration of psychology and neuroscience, but only a few are related to cross-cultural communication on social media. Conclusion: Scholars have mainly studied the reasons and implications of cultural communication on social media from the perspectives of cultural psychology and neuroscience separately. Keywords "culture" and "social media" generate more links in the hot map, and a large number of keywords of cultural psychology and neuroscience also gather in the hot map, which reflects the trend of integration in academic research. While cultural characteristics have changed with the development of new media and virtual communities, more research is needed to integrate the disciplines of culture, psychology, and neuroscience..